Efficacy of bioinoculants on biomass, nutritional status and yield of lemon grass (Cymbopogon citratus (DC.) Stapf.). - Kumar, Ashish; Gupta, A.; Aggarwal, A.; Bhargav, V. (Journal of Spices and Aromatic Crops, 2020)
In the present investigation, different bioinoculants were analysed to test their efficacy as bio-fertilizer value for medicinal plant i.e. Lemongrass (Cymbopogon citratus (DC.) Stapf.) under controlled conditions in a poly house. Bioinoculants including dominant Arbuscular Mycorhizal Fungi (Glomus mosseae and Acaulospora laevis) and Phosphate solubilizing Bacteria (Pseudomonas fluorescens) were taken in present experimentation. The independent roles of these bioinoculants or with different combinations were assessed on one month old saplings of C. citratus in pot conditions.The results showed that application of these bio-inoculants were very effective for growth responses, biomass, biochemical, yield parameters. A consortium of G. mosseae, A. laevis and P. fluorescens showed best results for plant height, root length and in increasing the biomass. Mycorrhization status was recovered highest in the consortium treatment. The biochemical and yield (biomass) parameters were also better with consortium. The findings of the present study are informative for herbalist, to use these efficient bioinoculants as bio-fertilizer for the better yield of C. citratus along with least adverse effects on microbial diversity and stability of soil as compared to commercially used inorganic fertilizers